Top food sources of energy and nutrients-to-limit among Latin Americans: Latin American Study of Nutrition and Health Study (ELANS) 2014–2015 - Fisberg, Regina Mara (2020)
Trabajo presentado en 13th European Nutrition Conference, FENS 2019, 15–18 October 2019, Malnutrition in an Obese World: European Perspectives